The Influence of Audit Quality, Independent Board of Commissioners and Managerial Ownership on Profit Management (Case Study on Companies Included in LQ45 in the Indonesia Sharia Stock Index in 2019 -2023) - Efendi, Erizal Candra; Meirison (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The primary goal of this research is to analyse the relationship between profit management and factors such managerial ownership, audit quality, and board of commissioners independence. Secondary sources are the backbone of this research. In particular, the LQ45 index members of the Indonesia sharia stock index for the years 2019"“2023, are the subject of this study. The data for this study came from a population of 180 individuals whose records were scanned by the company. A total of 95 participants participated in the survey, which used a purposive summarising technique. Using quantitative methodologies, this study tests theories about the impact of managerial ownership, audit quality, and an independent board of commissioners on profit management. The first estimate was supported by a sig value of 0.05 and a T value of 1.98638, indicating that the audit quality had a smaller impact on profit management than what was initially thought. As demonstrated by an A T value of -.1695 < 1.66515 and a sig value of 0.093 > 0.05, the independent board of commissioners did not significantly impact profit management. With a sig value of 0.118 > 0.05 and a T value of 1.1557 < 1.66515, partial managerial ownership does not significantly impact profit management. Both the individual and combined effects of audit quality, independent board of commissioners, and managerial ownership on profit management are statistically significant (F value of 3.140 < 2.70 and sig value of 0.029 < 0.05). There were additional variables that made up 93.6% of the total, even though audit quality, independent board of commissioners, and managerial ownership only made up 6.4%. According to the statistics given, profit management is significantly affected by audit quality, the independence of the board of commissioners, and managerial ownership.